Less than one millimeter under the great toe is enough to change balance ability in elite women handball players - Viseux, F.; Barbier, F.; Parreira, R.; Lemaire, A.; Villeneuve, P.; Leteneur, S. (Journal of Human Kinetics, 2019)
Team handball is a complex intermittent sport game, which requires several motor abilities and effective postural control. Objective evaluation of stabilometric variables may be interesting to assess and improve functional parameters by postural control management. The purpose of the study was to evaluate the effects of a small additional thickness placed under the great toe (TUGT) on the Centre of Pressure (CoP) parameters in elite women handball players. Fourteen elite women handball players voluntarily participated in this study. Two conditions were compared: TUGT 0 (control) and TUGT 0.8 mm; four variables were computed from the CoP displacements. A paired T-test was performed for each variable. This study concludes that a low focal additional thickness placed under both great toes has an effect on the CoP measures used to assess postural control during an unperturbed stance. These results suggest that a low TUGT could contribute to a change in balance ability, and may be of clinical interest. This brings new perspectives in the management of athletes to prevent injury risk and optimize performance.